DSP Implementation and Simulation of IM Drive Using Fuzzy Logic - Libor Stepanec; Pavel Brandstetter (Communications - Scientific letters of the University of Zilina, 2004)
This paper deals with vector-controlled induction motor drive, which uses fuzzy logic as a part of artificial intelligence. There are three phases: development, simulation and DSP implementation, which are discussed in this paper. In the first part of the paper fuzzy logic and development of the given problem are described. Next, there is a description of the used control structure. Important simulations were realised, which confirm the rightness of proposed structure and good behaviour of developed fuzzy controller. The simulation results are also given. In the end part of the paper, there are presented a control system with DSP TMS 320C40 and experimental results. There are also presented advantages of fuzzy logic and main features of used method are summarised too.